In Vitro and In Silico Evaluation of Antioxidant Activity of Muscle and Endoskeleton from Sepia officinalis - Daniella, Katherine; Ismail, Rafly Alif; Fahrudin, Fahri; Cing, Jap Mai; Alfarabi, Muhammad (RUMPHIUS, 2025)
Sepia officinalis, commonly known as cuttlefish, is one of the diverse marine organisms consumed for its high protein content. Amino acids, as the building blocks of proteins, can function as antioxidant compounds. The high amino acid content in cuttlefish makes it a potential natural source of antioxidants. However, the use of cuttlefish in medicine, particularly as an antioxidant source, remains limited in Indonesia. At present, cuttlefish is mainly utilized as a dietary protein source. The objective of this study was to evaluate the antioxidant activity of muscle and endoskeleton extracts from S. officinalis using the DPPH (2,2-diphenyl-1-picrylhydrazyl) assay in vitro. In addition, an in silico approach was employed to analyze the interaction of these extracts with myeloperoxidase, an oxidant-producing enzyme. The results demonstrated that both muscle and endoskeleton extracts were able to scavenge free radicals, showing DPPH inhibition ranging from 46.19% to 48.42%. The highest inhibition was observed at a concentration of 200 ppm for both extracts. Furthermore, in silico analysis revealed that tyrosine and phenylalanine were the key amino acids with antioxidant potential, as they inhibited myeloperoxidase activity and could reduce oxidant production by the enzyme. These findings highlight the potential of S. officinalis as a natural antioxidant source and support its future development as a functional food ingredient.